Education: The Key to Curb HIV and AIDS Epidemic - Bhatta, DN; Aryal, UR; Khanal, K (Kathmandu University Medical Journal, 2015)
Overwhelming impact has been established among different aspects and burden of incurable HIV and AIDS is increasing day-by-day globally. The aim of this article is to discuss the potential benefits and strengths of an education system in the absence of remedy and help to develop future strategies. Education has great impact on HIV and AIDS and vice-versa. An education plays a vital role to curb the transmission of HIV and AIDS thorough capacity building, provides information, reduces vulnerability, empowerment, improve life skill, maintain equity, reduce dependence, stigma, and discrimination, where are abundance foundations for HIV infection. HIV and AIDS has role for devastation of education system and level which has great impact on productivity, economic growth, demand, supply and daily life of human being. Low and middle income countries needs to be improve recording and reporting systems related to impact of HIV and AIDS on education. By analyzing preceding evidences, policy makers or governance feels to reformulate policies relating to education and health. Evidence based policy and program will be more useful to address distressing squall of epidemic. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12493 Kathmandu University Medical Journal Vol.11(2) 2013: 158-161